2021
DOI: 10.1101/2021.02.17.431740
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PEAK3 pseudokinase represents a pro-migratory and -invasive signalling scaffold

Abstract: The PEAK family of pseudokinases comprises PEAK1 and PEAK2 as well as the recently-identified PEAK3. PEAK1/2 play fundamental roles in regulating tyrosine kinase signal output and oncogenesis, while PEAK3 remains poorly-characterized. Here, we demonstrate that PEAK3 undergoes homotypic association as well as heterotypic interaction with PEAK1/2. PEAK3 also recruits ASAP1/2, Cbl and PYK2 and the adaptors Grb2 and CrkII, with binding dependent on PEAK3 dimerization. PEAK3 tyrosine phosphorylation on Y24 is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(83 reference statements)
1
3
0
Order By: Relevance
“…Since PYK2 is regulated by dimerization [ 26 ], its binding to PEAK3 might facilitate this activation mechanism. During the preparation of this manuscript, the Daly group reported a similar PEAK3 oncogenic function in breast epithelial cells and showed that PEAK3 tyrosine phosphorylation promotes GBR2 and ASAP1 binding [ 35 ], which is highly consistent with our proposed mechanism of PEAK3 oncogenic signaling.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Since PYK2 is regulated by dimerization [ 26 ], its binding to PEAK3 might facilitate this activation mechanism. During the preparation of this manuscript, the Daly group reported a similar PEAK3 oncogenic function in breast epithelial cells and showed that PEAK3 tyrosine phosphorylation promotes GBR2 and ASAP1 binding [ 35 ], which is highly consistent with our proposed mechanism of PEAK3 oncogenic signaling.…”
Section: Discussionsupporting
confidence: 77%
“…Mechanistically, our findings support a tyrosine phosphorylation-dependent PEAK3 signaling implicating the TK PYK2 ( Figure S9 ). For instance, PEAK3 may act a scaffold to bring PYK2 and ASAP1 together for efficient ASAP1 tyrosine phosphorylation, enabling AKT signaling [ 33 , 34 , 35 ]. Moreover, our results suggest that PEAK3 activates PYK2 through a SHED-dependent mechanism, as previously reported for PEAK2 activation of CSK [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One important question not addressed in our study is the mechanism of PEAK3 regulation. During the preparation of this manuscript, Daly et al reported a similar PEAK3 oncogenic function in breast epithelial cells and showed that PEAK3 tyrosine phosphorylation promotes GBR2 and ASAP1 binding (36). Although many upstream TKs, including SFKs, could phosphorylate PEAK3, our finding suggest that PYK2 phosphorylates PEAK3, like CSK phosphorylates PEAK2.…”
Section: Discussionmentioning
confidence: 49%